Taxonomic and faunistic remarks on European Ptilomyia Coquillett (Diptera: Ephydridae) - Stuke, Jens-Hermann (Zootaxa, 2021)
The number of species of Ptilomyia Coquillett, 1900 occurring in Europe is confirmed as three, with two previously recorded species being synonymised and one species being newly added: Ptilomyia shoka Mathis & Zatwarnicki, 2017 is herewith reported from Georgia for the first time. The available type material of European Ptilomyia species was examined and resulted in two new synonyms: Ptilomyia kairensis (Becker, 1903) = Atissa orsovana Enderlein, 1922 (syn. nov.) = Ptilomyia madeirensis Stuke 2012 (syn. nov.). The known distribution of all three valid European species is discussed, and records are listed from Croatia, Cyprus, Czech Republic, France, Georgia, Germany, Greece, Italy, Jordan, Morocco, Portugal and the United Arab Emirates. A key to the European species is provided and the male terminalia of all three species are illustrated.